Effects of tributyl citrate plasticizer on thermomechanical attributes of poly lactic acid - Izan Roshawaty Mustapa (Tanjong Malim, 2019)
Effects of tributyl citrate plasticizer on thermomechanical attributes of poly lactic acid by Izan Roshawaty Mustapa